The development and internal consistency of the comprehensive lower limb amputee socket survey in active lower limb amputees. (February 2019) - Gailey, Robert; Kristal, Anat; Lucarevic, Jennifer; Harris, Shane; Applegate, Brooks; Gaunaurd, Ignacio
Background: Prosthetic socket fit is an important element associated with successful ambulation and use of a prosthesis. Prosthetists and rehabilitation clinicians would benefit from an assessment tool that discriminates between and quantifies the multiple determinants that influence the lower limb amputee's performance and satisfaction of a prosthetic socket. Objectives: To determine the internal consistency of the comprehensive lower limb amputee socket survey, a new self-report measure of prosthetic socket satisfaction that quantifies suspension, stability, comfort, and appearance. Study design: Cross-sectional sample of active amputees. Methods: Interviews were conducted with prosthetists, physical therapists, and lower limb amputees to identify clinical concerns and common activities influencing socket fit. An expert panel of five clinicians reviewed the items and constructed the original version of the comprehensive lower limb amputee socket survey which was then administered to a convenience sample of 47 active lower limb amputees. Item analysis and Cronbach's alpha were used to determine the final version of the comprehensive lower limb amputee socket survey. Results: Following item raw score-to-total score correlation with Cronbach's alpha for comprehensive lower limb amputee socket survey determinants, internal consistency improved when nine questions were eliminated. Conclusion: The comprehensive lower limb amputee socket survey is a self-report measure of prosthetic socket satisfaction with very good internal consistency. Clinical relevance: When socket problems occur, the ability to determine the specific cause can reduce modification time, enhance socket fit, and promote patient satisfaction. A standardized multi-dimensional assessment measure of socket satisfaction enables prosthetists to quantify the multiple determinants of socket satisfaction, improve patient communication, and demonstrate the value of socket interventions.